COMMERCIAL BANKS’ FACILITIES AND SMALL AND MEDIUM SCALE ENTERPRISES GROWTH IN KWARA STATE - Kayode David KOLAWOLE (International Journal of Social and Educational Innovation)
Small and medium scale enterprises are engines of growth and catalysts for socio-economic development in both developing and developed countries. However, it has not performed admirably well because of inadequate banking facilities. This has affected the growth of small and medium scale enterprises in Kwara State. Hence, this study examined the effect of commercial banks on the growth of Small and Medium Scale Enterprises (SMEs) in Kwara state. Specifically, the study examined (i) the influence of commercial bank credit on SMEs growth in Kwara State and (ii) the impact of advisory services of commercial bank facilities on the growth of SMEs in Kwara State. The study employed primary data obtained through administered questionnaire to operators of small and medium scale enterprises. The study made use of both descriptive and inferential statistics such as frequencies, percentages and ordered logit and ordered probit regression to analyse the obtained data. At 0.05 level of significance the results of both the ordered logit and ordered probit regressions reveal that, commercial bank facilities such as loans, advisory services, collateral requirement, interest rate and banking inspection of SMEs are determinants of the growth of SMEs in Kwara State. The study therefore concluded that commercial banking facilities are significant determinants of the growth of SMEs in Kwara State. Hence, interest rate and other charges should be managed in a way that it will favor the growth of SMEs in Kwara state.